The transformative power of digital humanities in teaching family history online - Harman, Kristyn (Journal of University Teaching and Learning Practice, 2018)
This paper explores the transformative power of digital humanities in teaching family history online to large cohorts of Australian domestic students. It takes as a case study a unit developed specifically for students to learn about how to research their convict ancestors’ lives and how to situate their ancestors’ lived experiences within relevant wider contexts. Its focus is twofold. The convergence of rapidly expanding digital repositories and databases of family history-related information and increasingly sophisticated online teaching platforms and how this has facilitated a shift from face-to-face to fully online learning and teaching is examined. The ways in which this transformative change was engineered through the unit design, delivery, and evaluative processes are then canvassed. The case study demonstrates how, with thoughtful, well-structured, and innovative approaches to design and by adopting a bespoke delivery model for online delivery, students can readily learn to access and engage critically with extensive online resources and can be equipped with the digital tools to use these optimally and to their satisfaction.